Malpanuta d-ʼAbahata Suryaye d-ʻal ṣluta = The teaching of the Syrian fathers on prayer - Brock, Sebastian P. 1938- (Maṭbaʻta Suryayta d-Bar ʻEbraya d-Dayara d-Mar ʼEprem Suryaya, 1988)
Extracts from early Syriac authors on prayer and spirituality, edited with an introduction (translated from English) by S.P. Brock